STUDI KASUS SISWA UNDERACHIEVER DI SMA YAYASAN PERGURUAN HARAPAN MANDIRI MEDAN - Sabrini Mentari Rezeki (Psikologi Prima, 2019)
The objective of this study is to obtain a depiction of the characteristics of students who experience underachiever and the factors causing it. The method used in this research was qualitative method with case study research model. The data was collected using semi-structured interviews, observation and documentation. The subject of the research was a student who experienced underachiever. The data was analyzed using the Miles and Huberman model techniques. The conclusion was that HT experienced underachiever with the characteristics of low self-esteem and low academic self-concept. The factors which caused HT underachiever are strategies in learning, psychological conditions, emotional factors. Low motivational factors, psychosocial conditions factors, namely family conditions, parents do not pay attention, the father often gives punishment to HT and parents who often criticize HT are the factors causing underachiever.